Optimizing light guide plate (LGP) micro-grooves and micro-dots pattern using CO2 laser structuring: Influence of laser parameters and pattern arrangements on optical performances - Raja Murfiqah, Raja Mohd Fouzy; Norfazilasari, Yasman; Mohd Zairulnizam, Mohd Zawawi (Penerbit Akademia Baru, 2025)
This study investigates the effects of various direct CO2 laser structuring parameters on the formation of straight parallel micro-grooves on PMMA (Polymethyl methacrylate) substrates for light guide plate (LGP) application. Key parameters examined include laser power, laser scanning speed, and number of lasers passes. Then, based on our previous work, a comparative analysis on the effect of parallel micro-grooves and micro-dots pattern of different pitch on the luminance was evaluated. Then, the study further explored the influence of different micro-dots pattern arrangements and pitch, namely Micro-dots Type I (regular grid) and Micro-dots Type II (staggered hexagonal) on the optical luminance of the LGP. The former results shows that straight parallel micro-grooves exhibit higher luminance compared to micro-dots, based on observation of the physical brightness and luminance reading. The latter revealed that that smaller micro-dots pitch sizes and staggered hexagonal arrangements enhance luminance. This study provides a useful insight in understanding the relationship of laser parameters for the formation of micro-pattern and influences of pattern arrangements in the optimization of light distribution in PMMA LGP for applications such as displays and lighting systems.